Guillain-Barre syndrome, Fisher syndrome and Bickerstaff brainstem encephalitis: Understanding the pathogenesis - Shahrizaila, N.; Yuki, N. (Asean Neurological Assoc, 2010)
Guillain-Barre syndrome (GBS), Fisher syndrome (FS) and Bickerstaff brainstem encephalitis represent a spectrum of acute post-infectious immune-mediated diseases. GBS can present as acute inflammatory demyelinating neuropathy or acute motor axonal neuropathy (AMAN). The epidemiological association of Campylobacter jejuni infection and antiganglioside antibodies with AMAN and FS is well established. Gangliosides GM1 and GD1a, target molecules in AMAN, are identical to the terminal carbohydrate residues of C jejuni lipo-oligosaccharides. AMAN can be reproduced in rabbits sensitized with the gangliosides and lipo-oligosaccharides, thus verifying GBS as the first example of molecular mimicry in autoimmune diseases. Immunohistochemical studies on AMAN rabbit models demonstrated autoantibody binding at the nodes of Ranvier, triggering complement activation followed by formation of membrane attack complexes. This leads to the disappearance of sodium channel clusters, causing muscle weakness and axonal degeneration. Like AMAN, FS also displays molecular mimicry but between GQ1b and C jejuni lipo-oligosaccharides. The development of either AMAN or FS following C jejuni infection depends on which ganglioside-like lipo-oligosaccharides are expressed by C jejuni strains as a result of the bacterial genetic polymorphism. Bickerstaff brainstem encephalitis share common findings of anti-GQ1b antibodies with FS making the two disorders related, thus extending the spectrum of the GBS phenotype.